Polycarbonate resin composition and molded article comprising same
By adding special glass fibers and phenoxy resins or epoxy resins to the polycarbonate resin, the problem of the existing polycarbonate resins falling in a humid and heat environment and chemical medium is solved, and a high-strength, moisture and heat resistance and chemical resistance polycarbonate resin composition is realized.
Patent Information
- Application Number
- CN202380063354.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-02
- Filing Date
- 2023-07-27
- Publication Date
- 2025-04-11
AI Technical Summary
The existing polycarbonate resins are difficult to maintain high strength in humid and heat environments and chemical media, and their humidity and heat resistance and chemical resistance are insufficient.
By adding glass fibers containing a surface treatment agent and/or a bundling agent to the aromatic polycarbonate resin, and heating them at high temperatures to obtain a specific gas component, and using a phenoxy resin and/or an epoxy resin, a polycarbonate resin composition with excellent tensile strength, moisture and heat resistance, chemical resistance and processability is prepared.
A polycarbonate resin composition that can maintain high strength under a humid and heat environment and chemical medium is achieved, which significantly improves its moisture and heat resistance and chemical resistance, while maintaining good processability.
Smart Images

Figure CN119816558A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polycarbonate resin composition and a molded article thereof, wherein the polycarbonate resin composition is formed of an aromatic polycarbonate resin, glass fiber, and a phenoxy resin and / or an epoxy resin, wherein the glass fiber contains a surface treatment agent and / or a sizing agent, and a gas component obtained by heating at 600° C. for 12 seconds contains a carboxylic anhydride, or a gas component obtained by heating at 400° C. for 12 seconds contains a specific compound. More specifically, the present invention relates to a polycarbonate resin composition that is excellent in tensile strength, moisture and heat resistance, chemical resistance, and processability, and is suitable for parts that require high strength in various environments. Background Art
[0002] Polycarbonate resin is a resin with excellent heat resistance, impact resistance, dimensional stability, etc., and is widely used in the fields of electrical and electronic components, mechanical components, automotive components, OA equipment components, etc. In recent years, due to the continuous development of high performance and long life of products, there is a strong demand for resin materials to have high strength, especially to maintain high strength even when used for a long time in a hot and humid environment or in an environment where reagents are in contact.
[0003] Conventionally, in order to improve the mechanical properties such as tensile strength of polycarbonate resin, there are known methods of adding fibrous fillers (Patent Document 1), and methods of adding fibrous fillers and adhesion improvers to further improve strength (see Patent Documents 2 and 3). However, while improving mechanical properties such as tensile strength, there is no mention of moisture and heat resistance and chemical resistance, and it cannot be said that the solution to the above technical problems is fully disclosed.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 2683662
[0007] Patent Document 2: Japanese Patent Application Publication No. 2009-292953
[0008] Patent Document 3: Japanese Patent Application Publication No. 2013-221072 Summary of the invention
[0009] In view of the above circumstances, an object of the present invention is to provide a polycarbonate resin composition which is excellent in tensile strength, moisture and heat resistance, chemical resistance and processability and is suitable for parts which need to maintain high strength even in a moisture and heat environment or an environment in contact with reagents.
[0010] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that a polycarbonate resin composition having excellent tensile strength, moisture and heat resistance, chemical resistance and processability can be obtained by adding a glass fiber containing a surface treatment agent and / or a sizing agent and whose gas component obtained by heating at 600°C for 12 seconds contains carboxylic anhydride, or a glass fiber whose gas component obtained by heating at 400°C for 12 seconds contains a specific compound, and a phenoxy resin and / or an epoxy resin to an aromatic polycarbonate resin, thereby completing the present invention.
[0011] That is, the present invention is as follows.
[0012] 1. A polycarbonate resin composition, characterized in that it contains 20 to 130 parts by weight of (B) glass fiber (component B) and 1 to 10 parts by weight of (C) phenoxy resin and / or epoxy resin (component C) relative to 100 parts by weight of (A) aromatic polycarbonate resin (component A), component B contains at least one compound selected from a surface treatment agent and a sizing agent, and a gas component obtained by heating component B at 600° C. for 12 seconds contains carboxylic anhydride, or a gas component obtained by heating component B at 400° C. for 12 seconds contains a compound represented by the following general formula (1).
[0013]
[0014] [In the above general formula (1), n is an integer of 1 to 10, X each independently represents an alkylene group having 1 to 5 carbon atoms, and Y each independently represents an alkyl group having 1 to 5 carbon atoms.]
[0015] 2. The polycarbonate resin composition according to the above Item 1, wherein the carboxylic acid anhydride is 1,2,3,6-tetrahydrophthalic anhydride.
[0016] 3. The polycarbonate resin composition according to item 1 above, wherein X in the compound represented by the general formula (1) is an alkylene group having 3 carbon atoms.
[0017] 4. The polycarbonate resin composition according to item 1 or 3 above, wherein the compound represented by the general formula (1) is 4,8,12,16-tetraoxaeicosan-1-ol.
[0018] 5. The polycarbonate resin composition according to any one of the above items 1 to 4, wherein the component C is a bisphenol A type phenoxy resin and / or a bisphenol A type epoxy resin.
[0019] 6 . The polycarbonate resin composition according to claim 1 , further comprising 0.01 to 3 parts by weight of a phosphorus-based flame retardant (component D) based on 100 parts by weight of component A.
[0020] 7. The polycarbonate resin composition according to any one of Items 1 to 6, further comprising 0.01 to 35 parts by weight of (E) a flame retardant (component E) and 0.1 to 3 parts by weight of (F) an anti-drip agent (component F) based on 100 parts by weight of component A.
[0021] 8. The polycarbonate resin composition according to any one of the above 1 to 7, further comprising 1 to 20 parts by weight of (G) a liquid crystal polyester resin (component G) based on 100 parts by weight of the component A.
[0022] 9. The polycarbonate resin composition according to the above item 8, wherein the component G is a liquid crystal polyester resin containing a repeating unit derived from p-hydroxybenzoic acid and a repeating unit derived from 6-hydroxy-2-naphthoic acid.
[0023] 10. A molded article obtained by molding the polycarbonate resin composition according to any one of 1 to 9 above.
[0024] The polycarbonate resin composition of the present invention has excellent tensile strength, moisture and heat resistance, chemical resistance and processability. These properties are not available in the prior art, so the industrial effect of the present invention is very large. DETAILED DESCRIPTION
[0025] The present invention is described in detail below.
[0026] (Component A: aromatic polycarbonate resin)
[0027] The aromatic polycarbonate resin used as the A component in the present invention is to obtain by reacting dihydric phenol with a carbonate precursor. As an example of reaction method, the solid phase transesterification method of interfacial polymerization, melt transesterification, carbonate prepolymer and the ring-opening polymerization method of cyclic carbonate compounds etc. can be enumerated.
[0028] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and 2,2-bis(4-hydroxyphenyl)-1,1-bis(4-hydroxyphenyl)-2,3-dimethylcyclohexane. The preferred dihydric phenols include bis(4-hydroxyphenyl)alkanes, ...
[0029] In the present invention, in addition to bisphenol A-based polycarbonate, which is a general-purpose polycarbonate, special polycarbonate produced using other dihydric phenols may be used as the component A.
[0030] For example, polycarbonates (homopolymers or copolymers) using 4,4'-(m-phenylenediisopropylidene)diphenol (hereinafter, sometimes referred to as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter, sometimes referred to as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter, sometimes referred to as "BCF") as part or all of the dihydric phenol components are suitable for applications where the requirements for dimensional change due to water absorption and morphological stability are particularly strict. It is preferred that the dihydric phenol other than these BPAs be used in an amount of 5 mol% or more, particularly 10 mol% or more of the total dihydric phenol components constituting the polycarbonate.
[0031] In particular, when high rigidity and better hydrolysis resistance are required, the component A constituting the resin composition is preferably a copolymer polycarbonate of the following (1) to (3).
[0032] (1) A copolymer polycarbonate in which, in 100 mol % of the dihydric phenol component constituting the polycarbonate, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, further preferably 45 to 65 mol %) and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, further preferably 35 to 55 mol %).
[0033] (2) A copolymer polycarbonate in which, in 100 mol % of the dihydric phenol component constituting the polycarbonate, 10 to 95 mol % (more preferably 50 to 90 mol %, further preferably 60 to 85 mol %) of BPA and 5 to 90 mol % of BCF (more preferably 10 to 50 mol %, further preferably 15 to 40 mol %) are present.
[0034] (3) A copolymer polycarbonate in which, in 100 mol % of the dihydric phenol component constituting the polycarbonate, BPM accounts for 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and Bis-TMC accounts for 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %).
[0035] These special polycarbonates may be used alone or in combination of two or more thereof, or may be mixed with a general-purpose bisphenol A type polycarbonate.
[0036] The production methods and properties of these special polycarbonates are described in detail in, for example, Japanese Patent Application Laid-Open Nos. 6-172508, 8-27370, 2001-55435, and 2002-117580.
[0037] Among the various polycarbonates mentioned above, polycarbonates whose copolymer composition is adjusted so that the water absorption and Tg (glass transition temperature) are within the following ranges are particularly suitable for fields requiring morphological stability because the polymer itself has good hydrolysis resistance and is also particularly excellent in low warpage after molding.
[0038] (i) a polycarbonate having a water absorption of 0.05 to 0.15%, preferably 0.06 to 0.13%, and a Tg of 120 to 180°C, or
[0039] (ii) A polycarbonate having a Tg of 160 to 250°C, preferably 170 to 230°C, and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, more preferably 0.14 to 0.27%.
[0040] Here, the water absorption of polycarbonate is a value obtained by measuring the moisture content of a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm after immersion in water at 23° C. for 24 hours in accordance with ISO 62-1980. In addition, Tg (glass transition temperature) is a value obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121.
[0041] As the carbonate precursor, carbonyl halide, carbonic acid diester, halogenated formates, etc. can be used, and specific examples thereof include phosgene, diphenyl carbonate, and dihalogenated formates of dihydric phenols.
[0042] When utilizing interfacial polymerization to manufacture aromatic polycarbonate resin with above-mentioned dihydric phenol and carbonate precursor, as required, can use catalyzer, end-capping agent, antioxidant that is used to prevent dihydric phenol from oxidation etc.In addition, aromatic polycarbonate resin of the present invention comprises: the branched polycarbonate resin that is formed by the copolymerization of polyfunctional aromatic compound above trifunctional, the polyester carbonate resin that is formed by the copolymerization of difunctional carboxylic acid of aromatic or aliphatic (comprising alicyclic), the copolymerization polycarbonate resin that is formed by the copolymerization of difunctional alcohol (comprising alicyclic), and the polyester carbonate resin that is formed by the copolymerization of above-mentioned difunctional carboxylic acid and difunctional alcohol.In addition, also can be the mixture that more than 2 kinds of aromatic polycarbonate resin that obtains are mixed into.
[0043] The branched polycarbonate resin can impart anti-drip properties to the resin composition of the present invention. Examples of the trifunctional or higher polyfunctional aromatic compound used in the branched polycarbonate resin include phloroglucinol, phloroglucinol, or 4,6-dimethyl-2,4,6-tris(4-hydroxydiphenyl)-2-heptene, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methyl The present invention can be used in combination with triphenols such as 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol, tetrakis(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, or trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid and acid chlorides thereof, among which 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.
[0044] The content of the structural units derived from the polyfunctional aromatic compound in the branched polycarbonate is preferably 0.01 to 1 mol %, more preferably 0.05 to 0.9 mol %, and even more preferably 0.05 to 0.8 mol %, based on 100 mol % of the total of the structural units derived from the diphenol and the structural units derived from the polyfunctional aromatic compound.
[0045] In particular, in the case of the melt transesterification method, a branched structural unit may be generated as a side reaction. The amount of the branched structural unit is preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, and even more preferably 0.01 to 0.8 mol%, based on 100 mol% of the total of the structural units derived from the dihydric phenol. The ratio of the branched structure can be determined by 1 It was calculated by H-NMR measurement.
[0046] The aliphatic difunctional carboxylic acid is preferably an α,ω-dicarboxylic acid. As the aliphatic difunctional carboxylic acid, for example, a linear saturated aliphatic dicarboxylic acid such as sebacic acid (decane dioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, eicosanedioic acid, and an alicyclic dicarboxylic acid such as cyclohexanedicarboxylic acid can be preferably mentioned. As the difunctional alcohol, an alicyclic diol is more preferably used, for example, cyclohexanedimethanol, cyclohexanediol, and tricyclodecane dimethanol can be exemplified.
[0047] Reaction forms such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid phase transesterification method, and the ring-opening polymerization method of cyclic carbonate compounds as methods for producing aromatic polycarbonate resins are well known in various documents and patent publications.
[0048] When the polycarbonate resin composition of the present invention is produced, the viscosity average molecular weight (M) of the aromatic polycarbonate resin is not particularly limited, but is preferably 1×10 4 ~5×10 4 , more preferably 1.4×10 4 ~3×10 4 , and more preferably 1.4×10 4 ~2.4×10 4 , particularly preferably 1.7×10 4 ~2.1×10 4 . The viscosity average molecular weight is less than 1×10 4 Polycarbonate resins sometimes fail to provide good mechanical properties, especially high tensile strength. 4 The resin composition obtained by using the aromatic polycarbonate-based resin may have poor fluidity during injection molding, and thus has poor versatility.
[0049] It should be noted that the aromatic polycarbonate resin may be obtained by mixing an aromatic polycarbonate resin having a viscosity average molecular weight outside the above range. 4 ) in a polycarbonate resin, the entropy elasticity of the resin is improved. As a result, good processability is exhibited in gas-assisted molding and foaming molding used when the reinforced resin material is molded into a structural component. The improvement in processability is better than that of the branched polycarbonate. As a more preferred embodiment, component A may be used, which has a viscosity average molecular weight of 7×10 4 ~3×10 5 The polycarbonate resin (component A-1-1) and the viscosity average molecular weight 1×10 4 ~3×10 4 The aromatic polycarbonate resin (component A-1-2) is composed of an aromatic polycarbonate resin (component A-1-2) and has a viscosity average molecular weight of 1.6×10 4 ~3.5×10 4 A polycarbonate-based resin (component A-1) (hereinafter sometimes referred to as "polycarbonate-based resin containing a high molecular weight component").
[0050] In the polycarbonate resin containing a high molecular weight component (component A-1), the molecular weight of component A-1-1 is preferably 7×10 4 ~2×10 5 , more preferably 8×10 4 ~2×10 5 , more preferably 1×10 5 ~2×10 5 , particularly preferably 1×10 5 ~1.6×10 5 The molecular weight of component A-1-2 is preferably 1×10 4 ~2.5×10 4 , more preferably 1.1×10 4 ~2.4×10 4 , and more preferably 1.2×10 4 ~2.4×10 4 , particularly preferably 1.2×10 4 ~2.3×10 4 .
[0051] The polycarbonate resin containing a high molecular weight component (component A-1) can be obtained by mixing the above-mentioned component A-1-1 and component A-1-2 in various ratios and adjusting them in a manner to meet a predetermined molecular weight range. Preferably, the component A-1-1 is 2 to 40% by weight in 100% by weight of the component A-1, more preferably 3 to 30% by weight, further preferably 4 to 20% by weight, and particularly preferably 5 to 20% by weight.
[0052] In addition, as a method for preparing component A-1, the following methods can be mentioned: (1) a method of polymerizing component A-1-1 and component A-1-2 independently and mixing them; (2) a method of producing an aromatic polycarbonate resin showing a plurality of polymer peaks in a molecular weight distribution diagram based on a GPC method in the same system, as represented by the method disclosed in Japanese Patent Application Laid-Open No. 5-306336, and producing the above-mentioned aromatic polycarbonate resin in a manner that satisfies the conditions of component A-1 of the present invention; and (3) a method of mixing the aromatic polycarbonate resin obtained by the above-mentioned production method (production method of (2)) with component A-1-1 and / or component A-1-2 produced separately, etc.
[0053] The viscosity average molecular weight in the present invention is obtained as follows: First, using an Ostwald viscometer, a solution obtained by dissolving 0.7 g of polycarbonate in 100 ml of dichloromethane at 20° C. is used to obtain a specific viscosity (ηSP) calculated by the following formula:
[0054] Specific viscosity (ηSP) = (t-t0) / t0
[0055] [t0 is the dripping seconds of dichloromethane, t is the dripping seconds of the sample solution]
[0056] The viscosity average molecular weight M was calculated from the determined specific viscosity (ηSP) by the following mathematical formula.
[0057] ηSP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity)
[0058] [η] = 1.23 × 10 -4 M 0.83
[0059] c=0.7
[0060] It should be noted that the viscosity average molecular weight of the aromatic polycarbonate resin is calculated by the following method. That is, the composition is mixed with 20 to 30 times its weight of dichloromethane to dissolve the soluble components in the composition. The soluble components are collected by diatomaceous earth filtration. The solvent in the obtained solution is then removed. The solid after the solvent is removed is fully dried to obtain a solid of the component dissolved in dichloromethane. The specific viscosity at 20°C is calculated in the same manner as above from the solution obtained by dissolving 0.7 g of the above solid in 100 ml of dichloromethane, and the viscosity average molecular weight M is calculated in the same manner as above from the specific viscosity.
[0061] As the aromatic polycarbonate resin, a polycarbonate-polydiorganosiloxane copolymer resin may also be used. The polycarbonate-polydiorganosiloxane copolymer resin is preferably a copolymer resin prepared by copolymerizing a dihydric phenol represented by the following general formula (2) and a hydroxyaryl-terminated polydiorganosiloxane represented by the following general formula (4).
[0062]
[0063] [In the above general formula (2), R 1 and R 2 Each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkyloxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group and a carboxyl group. When there are a plurality of each, they may be the same or different. e and f are each an integer of 1 to 4. W is a single bond or at least one group selected from the groups represented by the following general formula (3).]
[0064]
[0065] [In the above general formula (3), R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 Each independently represents a group selected from a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and R 19 and R 20Each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkyloxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group. When there are a plurality of such groups, they may be the same or different. g is an integer of 1 to 10, and h is an integer of 4 to 7.]
[0066]
[0067] [In the above general formula (4), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, R 9 and R 10 Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number from 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.]
[0068] Examples of the dihydric phenol (I) represented by the general formula (2) include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)diphenylmethane, 9,9-bis(4-hydroxyphenyl)propane phenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyl diphenyl ether, 4,4'-sulfonyl diphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl-4,4'-sulfonyl diphenol, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfoxide, 4,4'-di Hydroxy-3,3'-dimethyl diphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyl diphenol, 4,4'-dihydroxy-3,3'-diphenyl diphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyl diphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.0 2,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane, and the like. Among them, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among them, 2,2-bis(4-hydroxyphenyl)propane is most preferred because of its excellent strength and good durability. In addition, these may be used alone or in combination of two or more.
[0069] As the hydroxyaryl-terminated polydiorganosiloxane represented by the general formula (4), for example, the following compounds are preferably used.
[0070]
[0071] Hydroxyaryl-terminated polydiorganosiloxane (II) is easily manufactured by subjecting phenols having olefinic unsaturated carbon-carbon bonds, preferably vinylphenol, 2-allylphenol, isopropenylphenol, 2-methoxy-4-allylphenol, to hydrosilylation at the end of a polysiloxane chain having a specified degree of polymerization. Among them, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred. Hydroxyaryl-terminated polydiorganosiloxane (II) preferably has a molecular weight distribution (Mw / Mn) of 3 or less. In order to exhibit further excellent low outgassing properties and low temperature impact properties during high temperature molding, the above molecular weight distribution (Mw / Mn) is more preferably 2.5 or less, and more preferably 2 or less. If the upper limit of the above preferred range is exceeded, the amount of outgassing generated during high temperature molding may be large and the low temperature impact resistance may be poor.
[0072] In order to achieve high impact resistance, the diorganosiloxane polymerization degree (p+q) of the hydroxyaryl-terminated polydiorganosiloxane (II) is preferably 10 to 300. The diorganosiloxane polymerization degree (p+q) is preferably 10 to 200, more preferably 12 to 150, and even more preferably 14 to 100. When the degree of polymerization is less than the lower limit of the preferred range, the impact resistance that is a characteristic of the polycarbonate-polydiorganosiloxane copolymer cannot be effectively exhibited, and when the degree of polymerization exceeds the upper limit of the preferred range, the appearance is poor.
[0073] The content of polydiorganosiloxane in the total weight of the polycarbonate-polydiorganosiloxane copolymer resin used in component A is preferably 0.1 to 50% by weight. The content of the polydiorganosiloxane component is more preferably 0.5 to 30% by weight, and further preferably 1 to 20% by weight. When the content is above the lower limit of the preferred range, the impact resistance and flame retardancy are excellent. When the content is below the upper limit of the preferred range, the molding conditions are not easily affected, and a stable appearance is easily obtained. The degree of polymerization of the polydiorganosiloxane and the content of the polydiorganosiloxane can be adjusted by 1 It was calculated by H-NMR measurement.
[0074] In the present invention, the hydroxyaryl-terminated polydiorganosiloxane (II) may be used alone or in combination of two or more.
[0075] Furthermore, other comonomers other than the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) may be used in an amount of 10% by weight or less based on the total weight of the copolymer without hindering the present invention.
[0076] In the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared in advance by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkali solution.
[0077] When generating the oligomer of dihydric phenol (I), the total amount of dihydric phenol (I) used in the method of the present invention can be formed into oligomers at one time, or a part of it can be added as a post-added monomer as a reaction raw material in the interfacial polycondensation reaction of the latter stage. The post-added monomer refers to a monomer added in order to quickly carry out the polycondensation reaction of the latter stage, and does not need to be added when it is not necessary.
[0078] The method of the oligomer production reaction is not particularly limited, but is usually preferably a method in which the reaction is carried out in a solvent in the presence of an acid binder.
[0079] The ratio of the carbonate-forming compound to be used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. In addition, when a gaseous carbonate-forming compound such as phosgene is used, it is preferably blown into the reaction system.
[0080] As above-mentioned acid binding agent, for example, organic bases such as alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, pyridine or their mixture etc. can be used. The usage ratio of acid binding agent is also as above-mentioned just as long as the stoichiometric ratio (equivalent) of reaction is considered and suitably determined. Specifically, preferably use the acid binding agent that is 2 equivalents or slightly excessive compared with 2 equivalents with respect to the mole number (usually 1 mole is equivalent to 2 equivalents) of the dihydric phenol (I) that is used to form oligomer.
[0081] As the above-mentioned solvent, a solvent inactive to various reactions, such as a solvent used in the manufacture of known polycarbonates, can be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents represented by methylene chloride and chlorobenzene. It is particularly preferred to use halogenated hydrocarbon solvents such as methylene chloride.
[0082] The reaction pressure for generating oligomers is not particularly limited and may be any one of normal pressure, pressurization, and reduced pressure. It is usually advantageous to conduct the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C. In most cases, water cooling or ice cooling is preferred because of the heat generated by polymerization. The reaction time is affected by other conditions and cannot be generalized. It is usually carried out within 0.2 to 10 hours. The pH range of the oligomer generation reaction is the same as the known interfacial reaction conditions, and the pH is usually adjusted to 10 or more.
[0083] In the present invention, after a mixed solution containing oligomers of a dihydric phenol (I) having a terminal chloroformate group is obtained, a hydroxyaryl-terminated polydiorganosiloxane (II) represented by the general formula (4) which has been highly purified to have a molecular weight distribution (Mw / Mn) of 3 or less is added to the dihydric phenol (I) while stirring the mixed solution, and the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer are subjected to interfacial polycondensation to obtain a polycarbonate-polydiorganosiloxane copolymer.
[0084]
[0085] (In the above general formula (4), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, R9 and R 10 Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number from 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.
[0086] When carrying out interfacial polycondensation reaction, it is possible to consider that the stoichiometric ratio (equivalent) of the reaction is appropriately added with an acid binding agent. As an acid binding agent, for example, organic bases such as alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, pyridine, or mixtures thereof, etc. can be used. Specifically, when a part of the hydroxyaryl-terminated polydiorganosiloxane (II) or the dihydric phenol (I) as described above is added as a post-addition monomer in the reaction stage, it is preferred to use a total molar number (usually 1 mole is equivalent to 2 equivalents) of 2 equivalents or a slightly excessive alkali compared to 2 equivalents relative to the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) of the post-addition part.
[0087] The polycondensation of the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) by an interfacial polycondensation reaction is carried out by vigorously stirring the mixed liquid.
[0088] In the above-mentioned polymerization reaction, a terminal terminator or a molecular weight regulator is usually used. As the terminal terminator, compounds having a monophenolic hydroxyl group can be cited, and in addition to common phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., long-chain alkylphenols, aliphatic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl esters, alkyl ether phenols, etc. can also be exemplified. The amount used is 100 to 0.5 moles, preferably 50 to 2 moles, relative to 100 moles of all diphenol compounds used. Of course, two or more compounds can also be used in combination.
[0089] In order to promote the polycondensation reaction, a catalyst such as a tertiary amine such as triethylamine or a quaternary ammonium salt may be added.
[0090] The reaction time of the above polymerization reaction is preferably 30 minutes or longer, more preferably 50 minutes or longer. If desired, a small amount of an antioxidant such as sodium sulfite or hydrogen sulfide may be added.
[0091] A branching agent can be used together with the above-mentioned dihydric phenolic compound to prepare a branched polycarbonate-polydiorganosiloxane. Examples of the trifunctional or higher polyfunctional aromatic compound used in the branched polycarbonate-polydiorganosiloxane copolymer resin include phloroglucinol, phloroglucinol, or 4,6-dimethyl-2,4,6-tris(4-hydroxydiphenyl)-2-heptene, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)ethane, )-4-methylphenol, 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol and other triphenols, tetrakis(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, or trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid and their acid chlorides, among which 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred. The ratio of the multifunctional compound in the branched polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, further preferably 0.01 to 0.8 mol%, and particularly preferably 0.05 to 0.4 mol% in the total amount of the aromatic polycarbonate-polydiorganosiloxane copolymer resin. 1 It was calculated by H-NMR measurement.
[0092] The reaction pressure can be any of reduced pressure, normal pressure, and pressurized pressure, and can usually be appropriately carried out under normal pressure or the self-pressure of the reaction system. The reaction temperature is selected from the range of -20 to 50°C. In most cases, water cooling or ice cooling is preferred because of the heat generated by polymerization. The reaction time varies depending on other conditions such as the reaction temperature, so it cannot be generally specified, and is usually carried out within 0.5 to 10 hours.
[0093] Depending on circumstances, the obtained polycarbonate-polydiorganosiloxane copolymer resin may be appropriately subjected to physical treatment (mixing, classification, etc.) and / or chemical treatment (polymerization reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a polycarbonate-polydiorganosiloxane copolymer resin having a desired reduced viscosity [ηSP / c].
[0094] The obtained reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods, and recovered as a polycarbonate-polydiorganosiloxane copolymer resin of the desired purity (purity). The average size of the polydiorganosiloxane domain in the polycarbonate-polydiorganosiloxane copolymer resin molded product is preferably in the range of 1 to 40 nm. The above average size is more preferably 1 to 30 nm, and further preferably 5 to 25 nm. When it is less than the lower limit of the above preferred range, impact resistance and flame retardancy may not be fully exerted. If it exceeds the upper limit of the above preferred range, impact resistance may not be stably exerted.
[0095] The average domain size and normalized dispersion of the polydiorganosiloxane domain of the polycarbonate-polydiorganosiloxane copolymer resin molded product of the present invention are evaluated by small angle X-ray scattering (SAXS). Small angle X-ray scattering refers to a method for measuring diffuse reflection and diffraction generated in a small angle region within a scattering angle (2θ) of less than 10°. In the small angle X-ray scattering method, if there are regions with different electron densities of about 1 to 100 nm in size in a substance, the diffuse scattering of X-rays is measured based on the difference in electron density. The particle size of the object to be measured is calculated based on the scattering angle and the scattering intensity. In the case of a polycarbonate-polydiorganosiloxane copolymer resin having an aggregate structure in which polydiorganosiloxane domains are dispersed in a matrix of a polycarbonate polymer, diffuse scattering of X-rays is generated due to the difference in electron density between the polycarbonate matrix and the polydiorganosiloxane domains. The scattering intensity I at each scattering angle (2θ) in the range of scattering angle (2θ) less than 10° is measured, and a small-angle X-ray scattering diagram is measured. It is assumed that the polydiorganosiloxane domain is a spherical domain and there is a difference in particle size distribution. According to the assumed particle size and the assumed particle size distribution model, a commercially available analysis software is used for simulation to obtain the average size and particle size distribution (standardized dispersion) of the polydiorganosiloxane domain. According to the small-angle X-ray scattering method, the average size and particle size distribution of the polydiorganosiloxane domain dispersed in the matrix of the polycarbonate polymer, which cannot be accurately measured by observation using a transmission electron microscope, can be measured with high precision, simplicity and good reproducibility. The average domain size refers to the number average of the sizes of each domain. The standardized dispersion refers to a parameter obtained by standardizing the breadth of the particle size distribution with the average size. Specifically, it is a value obtained by standardizing the dispersion of the polydiorganosiloxane domain size with the average domain size, and is represented by the following formula (1).
[0096] Standardized dispersion (%) = δ / D av …(1)
[0097] In the above formula (1), δ is the standard deviation of the polydiorganosiloxane domain size, and Dav is the average domain size.
[0098] The terms "average domain size" and "normalized dispersion" used in connection with the present invention refer to the values measured by measuring the 1.0 mm thickness portion of the three-layer board prepared by the method described in the examples using the above-mentioned small angle X-ray scattering method. In addition, the analysis is performed using an isolated particle model that does not consider the interaction between particles (interparticle interference).
[0099] (Component B: Glass fiber)
[0100] As the glass fiber used as component B in the present invention, preferred examples include glass fibers with a circular cross-section, flat cross-section glass fibers in which the average value of the major diameter of the fiber long cross-section is 5 to 20 μm and the average value of the ratio of the major diameter to the minor diameter (major diameter / minor diameter) is 1.5 to 8, and glass milled fibers. In particular, from the perspective of tensile strength, glass fibers with a circular cross-section and flat cross-section glass fibers in which the average value of the major diameter of the fiber long cross-section is 5 to 20 μm and the average value of the ratio of the major diameter to the minor diameter (major diameter / minor diameter) is 1.5 to 8 are more preferred.
[0101] The glass composition of the glass fiber can be various glass compositions represented by A glass, C glass and E glass, etc., without particular limitation. The glass fiber can contain components such as TiO2, SO3 and P2O5 as required. Among these, E glass (alkali-free glass) is more preferred.
[0102] The glass fiber contains at least one compound selected from a surface treatment agent and a sizing agent, and the gas component obtained by heating the glass fiber at 600°C for 12 seconds contains carboxylic anhydride, or the gas component obtained by heating the glass fiber at 400°C for 12 seconds contains a compound represented by the following general formula (1).
[0103]
[0104] (In the above general formula (1), n is an integer of 1 to 10, X each independently represents an alkylene group having 1 to 5 carbon atoms, and Y each independently represents an alkyl group having 1 to 5 carbon atoms.)
[0105] Examples of the carboxylic anhydride include maleic anhydride, itaconic anhydride, succinic anhydride, phthalic anhydride, 1,2,3,6-tetrahydrophthalic anhydride, glutaric anhydride, dodecenylsuccinic anhydride, and chlorendic anhydride.
[0106] X in the above general formula (1) is preferably an alkylene group having 3 carbon atoms.
[0107] In addition, examples of the compound represented by the general formula (1) include 4,8,12,16-tetraoxaicosan-1-ol, 2,5,8,11-tetraoxatetradecan-13-ol, 4,7,10-trimethyl-2-propanol, 1-(2-(2-methoxy-1-methylethoxy)-1-methylethoxy)propane, and 1,2-bis(2-methoxy-2-methylethoxy), and 4,8,12,16-tetraoxaicosan-1-ol is preferred.
[0108] It is believed that the carboxylic anhydride contained in the gas component obtained by heating at 600°C for 12 seconds or the compound represented by the general formula (1) contained in the gas component obtained by heating at 400°C for 12 seconds originates from the surface treatment agent and sizing agent contained in the glass fiber, and comes from the acid component or acid anhydride component contained in a part of the structure of the surface treatment agent and sizing agent.
[0109] The component from the compound represented by the carboxylic anhydride or the general formula (1) is an acid copolymer, having a carboxylic acid group or a carboxylic anhydride group. It is believed that these functional groups form a firm covalent bond with glass fiber by reacting with the terminal functional groups of the phenoxy resin and / or epoxy resin as the C component, so that the adhesion of the B component and the C component is improved. On the other hand, when the C component is especially bisphenol A type, the affinity with the aromatic polycarbonate resin as the A component is high. As a result, the adhesion of the A component and the B component is improved through the C component, and by using the glass fiber with such characteristics, the moisture heat resistance and chemical resistance of the polycarbonate resin composition can be greatly improved.
[0110] The gas components are measured in accordance with the method described in the examples below. However, if the equipment described in the examples is difficult to obtain due to being out of print, other equipment with the same performance may be used for measurement.
[0111] The content of component B is 20 to 130 parts by weight, preferably 30 to 120 parts by weight, and more preferably 40 to 120 parts by weight relative to 100 parts by weight of component A. When the content of component B is less than 20 parts by weight, the improvement of tensile strength is insufficient. On the other hand, when it exceeds 130 parts by weight, processability decreases.
[0112] (Component C: phenoxy resin and / or epoxy resin)
[0113] Examples of the phenoxy resin used as the component C in the present invention include phenoxy resins represented by the following general formula (5).
[0114]
[0115] (In the formula, X is at least one group selected from the groups represented by the following general formula (6), Y is a hydrogen atom or a residue of a compound that reacts with a hydroxyl group, and n is an integer greater than 0.)
[0116]
[0117] (In the formula, Ph represents a phenyl group.)
[0118] In the above general formula (5), as the compound that reacts with the hydroxyl group, esters, carbonates, compounds having epoxy groups, etc., carboxylic anhydrides, acyl halides, compounds having isocyanate groups, etc., etc. can be cited. As esters, intramolecular esters are particularly preferred, for example, caprolactone, etc. can be cited. In the phenoxy resin represented by the above general formula (4), the compound in which Y is a hydrogen atom can be easily manufactured from dihydric phenols and epichlorohydrin. In addition, the compound in which Y is a residue of a compound that reacts with the hydroxyl group can be easily manufactured by mixing a phenoxy resin manufactured from dihydric phenols and epichlorohydrin and the compound that reacts with the above hydroxyl group under heating.
[0119] Examples of the epoxy resin used as the component C in the present invention include epoxy resins represented by the following general formula (7).
[0120]
[0121] (Wherein, X and n are the same as in formula (5).)
[0122] The epoxy resin represented by the general formula (7) can be easily produced from dihydric phenols and epichlorohydrin. As dihydric phenols, bisphenol A type epoxy resins such as 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 1,1-bis(4-hydroxyphenyl)ethane or 4,4'-dihydroxybiphenyl can be used.
[0123] Among these phenoxy resins and epoxy resins, particularly preferred embodiments include bisphenol A type phenoxy resins and / or bisphenol A type epoxy resins.
[0124] As phenoxy resin and epoxy resin, commercial products can also be used. As commercial products of phenoxy resin (bisphenol A type), PKHB (manufactured by Gabriel Phenoxies, Mw=32000), PKHH (manufactured by Gabriel Phenoxies, Mw=52000), PKFE (manufactured by Gabriel Phenoxies, Mw=60000) and the like can be cited. In addition, as commercial products of epoxy resin (bisphenol A type), jER1256 (manufactured by Mitsubishi Chemical Corporation, Mw=50000) and the like can be cited.
[0125] The weight average molecular weight of the phenoxy resin and the epoxy resin is not particularly limited, but is preferably 5000 to 100000, more preferably 8000 to 80000, and further preferably 10000 to 50000. When the weight average molecular weight is in the range of 5000 to 100000, mechanical properties may be particularly good.
[0126] The content of component C is 1 to 10 parts by weight, preferably 1 to 7 parts by weight, and more preferably 2 to 6 parts by weight relative to 100 parts by weight of component A. When the content exceeds the above range and is too small, tensile strength, moisture and heat resistance, and chemical resistance deteriorate. On the other hand, when the content exceeds the above range, processability deteriorates.
[0127] (Component D: phosphorus stabilizer)
[0128] The polycarbonate resin composition of the present invention may contain a phosphorus-based stabilizer as a component D. The phosphorus-based stabilizer improves thermal stability during manufacturing or molding, and improves mechanical properties, color tone and molding stability. Examples of the phosphorus-based stabilizer include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid and their esters, and tertiary phosphines. Specifically, as phosphite compounds, for example, triphenyl phosphite, tris(nonylphenyl) phosphite, tridecyl phosphite, trioctyl phosphite, tri(octadecyl) phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tris(diethylphenyl) phosphite, tris(diisopropylphenyl) phosphite, tris( The invention also includes the following: bis(2,4-di-tert-butylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris(2,6-di-tert-butylphenyl) phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl) pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl) pentaerythritol diphosphite, and dicyclohexyl pentaerythritol diphosphite. In addition, as other phosphite compounds, phosphite compounds having a cyclic structure that react with dihydric phenols can also be used. For example, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl) phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl) phosphite, 2,2'-methylenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl) phosphite, 2,2'-methylenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl) phosphite, 2,2'-ethylenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl) phosphite, and the like can be mentioned. Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, triethyl phosphonoacetate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenylcresyl phosphate, diphenylmono-o-biphenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, and the like, with triphenyl phosphate, trimethyl phosphate, and triethyl phosphonoacetate being preferred.
[0129] Examples of the phosphite compound include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphite, bis(2,4-di-tert-butylphenyl)-4-phenyl -phenyl phosphite, bis(2,4-di-tert-butylphenyl)-3-phenyl-phenyl phosphite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenyl phosphite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenyl phosphite, bis(2,6-di-tert-butylphenyl)-3-phenyl-phenyl phosphite, etc., preferably tetrakis(di-tert-butylphenyl)-biphenylene diphosphite, bis(di-tert-butylphenyl)-phenyl-phenyl phosphite, more preferably tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphite, bis(2,4-di-tert-butylphenyl)-phenyl-phenyl phosphite. The above-mentioned phosphite compounds can be used in combination with the above-mentioned phosphite compounds having an aryl group substituted with two or more alkyl groups, so they are preferred. As phosphonate compounds, dimethyl phenylphosphonate, diethyl phenylphosphonate and dipropyl phenylphosphonate can be mentioned. Examples of tertiary phosphines include triethylphosphine, tripropylphosphine, tributylphosphine, trioctylphosphine, tripentylphosphine, dimethylphenylphosphine, dibutylphenylphosphine, diphenylmethylphosphine, diphenyloctylphosphine, triphenylphosphine, tri-p-tolylphosphine, trinaphthylphosphine and diphenylbenzylphosphine. A particularly preferred tertiary phosphine is triphenylphosphine. The above-mentioned phosphorus-based stabilizers may be used alone or in combination of two or more. Among the above-mentioned phosphorus-based stabilizers, it is preferred to use an alkyl phosphate compound represented by triethyl phosphonoacetate. In addition, the combination of the above-mentioned alkyl phosphate compound with a phosphite compound and / or a phosphite compound is also a preferred method.
[0130] The content of component D is preferably 0.01 to 3 parts by weight, more preferably 0.01 to 1 part by weight, and further preferably 0.02 to 0.1 parts by weight relative to 100 parts by weight of component A. If the content of component D exceeds 3 parts by weight, the moisture and heat resistance may deteriorate. On the other hand, if it is less than 0.01 parts by weight, the tensile strength may not be improved.
[0131] (Component E: flame retardant)
[0132] The polycarbonate resin composition of the present invention may be formulated with a flame retardant. Examples of the flame retardant include (i) organic metal salt flame retardants (e.g., organic sulfonic acid alkali (earth) metal salts, organic boric acid metal salt flame retardants, and organic stannic acid metal salt flame retardants), (ii) organic phosphorus flame retardants (e.g., monophosphate compounds, phosphate oligomer compounds, phosphonate oligomer compounds, phosphazene oligomer compounds, and phosphonamide compounds containing organic groups), (iii) organic silicon flame retardants composed of organic silicon compounds, and (iv) halogen flame retardants, among which organic metal salt flame retardants and halogen flame retardants are preferred. They may be used alone or in combination. The content of component E is preferably 0.01 to 35 parts by weight relative to 100 parts by weight of component A.
[0133] (i) Organic metal salt flame retardants
[0134] The organic metal salt compound is preferably an alkali (earth) metal salt of an organic acid having 1 to 50 carbon atoms, preferably 1 to 40 carbon atoms, and preferably an organic sulfonic acid alkali (earth) metal salt. The organic sulfonic acid alkali (earth) metal salt includes a metal salt of a fluorinated alkyl sulfonic acid such as a metal salt of a perfluoroalkyl sulfonic acid having 1 to 10 carbon atoms, preferably 2 to 8 carbon atoms, and an alkali metal or alkaline earth metal, and a metal salt of an aromatic sulfonic acid having 7 to 50 carbon atoms, preferably 7 to 40 carbon atoms, and an alkali metal or alkaline earth metal. As alkali metals constituting the metal salt, lithium, sodium, potassium, rubidium and cesium can be cited, and as alkaline earth metals, beryllium, magnesium, calcium, strontium and barium can be cited. Alkali metals are more preferred. Among the above-mentioned alkali metals, when the transparency requirement is higher, rubidium and cesium with larger ionic radius are preferred. On the other hand, because they are not universal or difficult to purify, the result is sometimes disadvantageous in terms of cost. On the other hand, metals with smaller ionic radius such as lithium and sodium are sometimes disadvantageous in terms of flame retardancy. The alkali metal used in the alkali metal sulfonate can be selected in consideration of these factors, but potassium sulfonate having excellent property balance is most preferred in all aspects. The above potassium salt may be used in combination with an alkali metal sulfonate composed of other alkali metals.
[0135] Specific examples of perfluoroalkylsulfonic acid alkali metal salts include potassium trifluoromethanesulfonate, potassium perfluorobutanesulfonate, potassium perfluorohexanesulfonate, potassium perfluorooctanesulfonate, sodium pentafluoroethanesulfonate, sodium perfluorobutanesulfonate, sodium perfluorooctanesulfonate, lithium trifluoromethanesulfonate, lithium perfluorobutanesulfonate, lithium perfluoroheptanesulfonate, cesium trifluoromethanesulfonate, cesium perfluorobutanesulfonate, cesium perfluorooctanesulfonate, cesium perfluorohexanesulfonate, rubidium perfluorobutanesulfonate, and rubidium perfluorohexanesulfonate, and these can be used alone or in combination of two or more. Among them, the number of carbon atoms in the perfluoroalkyl group is preferably in the range of 1 to 18, more preferably in the range of 1 to 10, and still more preferably in the range of 1 to 8.
[0136] Among these, potassium perfluorobutanesulfonate is particularly preferred. A considerable amount of fluoride ions (F - ). The presence of the above-mentioned fluorine ions will become a factor that reduces flame retardancy, so it is preferably reduced as much as possible. The ratio of the above-mentioned fluorine ions can be measured by ion chromatography. The content of fluorine ions is preferably less than 100 ppm, more preferably less than 40 ppm, and particularly preferably less than 10 ppm. In addition, it is preferably more than 0.2 ppm in terms of manufacturing efficiency. The perfluoroalkylsulfonic acid alkali (earth) metal salt with reduced fluorine ion content can be manufactured by the following methods: a method in which the manufacturing method uses a known manufacturing method and reduces the amount of fluorine ions contained in the raw materials when manufacturing fluorine-containing organic metal salts; a method in which the hydrogen fluoride obtained by the reaction is removed by the gas generated during the reaction or by heating; and a method in which the amount of fluorine ions is reduced by purification methods such as recrystallization and reprecipitation when manufacturing fluorine-containing organic metal salts. In particular, since organic metal salt-based flame retardants are more easily soluble in water, it is preferably manufactured using ion exchange water, especially water that satisfies a resistance value of more than 18 MΩ·cm, that is, a conductivity of about 0.55μS / cm or less, and dissolves it at a temperature higher than room temperature for washing, and then cools it to recrystallize it.
[0137] Specific examples of the aromatic sulfonic acid alkali (earth) metal salt include, for example, disodium diphenyl sulfide-4,4'-disulfonate, dipotassium diphenyl sulfide-4,4'-disulfonate, potassium isophthalic acid-5-sulfonate, sodium isophthalic acid-5-sulfonate, polyethylene terephthalate polysulfonate polysodium, 1-methoxynaphthalene-4-sulfonate calcium, 4-dodecylphenylene oxide disodium disulfonate, poly(2,6-dimethylphenylene oxide) polysulfonate polysodium, poly(1,3-phenylene oxide) polysulfonate polysodium, poly(1,4-phenylene oxide) polysulfonate polysodium, poly(2,6-diphenylphenylene oxide) polysulfonate polypotassium, poly(2-fluoro-6-butylphenylene oxide) polysulfonate lithium, and potassium sulfonate of benzene sulfonate. , sodium benzenesulfonate, strontium benzenesulfonate, magnesium benzenesulfonate, dipotassium p-terephthalenesulfonate, dipotassium naphthalene-2,6-disulfonate, calcium biphenyl-3,3'-disulfonate, sodium diphenylsulfone-3-sulfonate, potassium diphenylsulfone-3-sulfonate, dipotassium diphenylsulfone-3,3'-disulfonate, dipotassium diphenylsulfone-3,4'-disulfonate, sodium α,α,α-trifluoroacetophenone-4-sulfonate, dipotassium benzophenone-3,3'-disulfonate, disodium thiophene-2,5-disulfonate, dipotassium thiophene-2,5-disulfonate, calcium thiophene-2,5-disulfonate, sodium benzothiophenesulfonate, potassium diphenylsulfoxide-4-sulfonate, formaldehyde condensate of sodium naphthalenesulfonate, and formaldehyde condensate of sodium anthracenesulfonate. Among these aromatic sulfonic acid alkali (earth) metal salts, potassium salts are particularly preferred. Among these aromatic sulfonic acid alkali (earth) metal salts, potassium diphenyl sulfone-3-sulfonate and dipotassium diphenyl sulfone-3,3'-disulfonate are preferred, and a mixture thereof (the weight ratio of the former to the latter is 15 / 85 to 30 / 70) is particularly preferred.
[0138] As organic metal salts other than alkali (earth) metal salts of sulfonic acid, alkali (earth) metal salts of sulfates and alkali (earth) metal salts of aromatic sulfonamides can be appropriately exemplified. As alkali (earth) metal salts of sulfates, alkali (earth) metal salts of sulfates of monohydric and / or polyhydric alcohols can be particularly cited, and as the sulfates of the above-mentioned monohydric and / or polyhydric alcohols, methyl sulfate, ethyl sulfate, lauryl sulfate, hexadecyl sulfate, sulfates of polyoxyethylene alkylphenyl ether, mono / di / tri / tetrasulfate of pentaerythritol, sulfates of lauric acid monoglyceride, sulfates of palmitic acid monoglyceride, and sulfates of stearic acid monoglyceride can be cited. As alkali (earth) metal salts of these sulfates, alkali (earth) metal salts of lauryl sulfate can be preferably cited. As the alkali (earth) metal salt of aromatic sulfonamide, for example, saccharin, N-(p-tolylsulfonyl)-p-toluenesulfonyl imide, N-(N'-benzylaminocarbonyl)sulfonyl imide and alkali (earth) metal salt of N-(phenylcarboxyl)sulfonyl imide can be mentioned. The content of the organic metal salt flame retardant is preferably 0.01 to 1 part by weight, more preferably 0.01 to 0.5 part by weight, and further preferably 0.01 to 0.3 part by weight relative to 100 parts by weight of component A.
[0139] (ii) Organic phosphorus flame retardants
[0140] As the organophosphorus flame retardant, aryl phosphate compounds and phosphazene compounds are preferably used. These organophosphorus flame retardants have a plasticizing effect and are therefore advantageous in improving processability. The aryl phosphate compound can use various phosphate compounds known as flame retardants in the past, and more preferably one or more phosphate compounds represented by the following general formula (8) are cited.
[0141]
[0142] (X in formula (8) is a dihydric phenol residue derived from a dihydroxy compound selected from the group consisting of hydroquinone, resorcinol, bis(4-hydroxydiphenyl)methane, bisphenol A, dihydroxydiphenyl, dihydroxynaphthalene, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone and bis(4-hydroxyphenyl)sulfide, n is an integer of 0 to 5, or in the case of a mixture of phosphoric acid esters having different n numbers, it is the average value thereof, R 1 , R 2 , R 3 and R 4 Each is independently a monohydric phenol residue derived from an aromatic group selected from phenol, cresol, xylenol, isopropylphenol, butylphenol and p-cumylphenol.)
[0143] The phosphate compound of the general formula (8) may be a mixture of compounds having different n numbers. In the case of such a mixture, the average n number is preferably 0.5 to 1.5, more preferably 0.8 to 1.2, further preferably 0.95 to 1.15, and particularly preferably 1 to 1.14.
[0144] Preferred specific examples of the dihydric phenol from which X in the general formula (8) is derived include resorcinol, bisphenol A and dihydroxydiphenyl. Among them, resorcinol and bisphenol A are preferred.
[0145] As the derivative of R in the above general formula (8) 1 , R 2 , R 3 and R 4 Preferred specific examples of the monohydric phenol include phenol, cresol, xylenol, and 2,6-dimethylphenol, among which phenol and 2,6-dimethylphenol are preferred.
[0146] As specific examples of the phosphate compounds of the above-mentioned general formula (8), suitable ones include monophosphate compounds such as triphenyl phosphate and tris(2,6-xylyl) phosphate, and phosphate oligomers mainly composed of resorcinol bis((2,6-xylyl) phosphate), phosphate oligomers mainly composed of 4,4-dihydroxydiphenyl bis(diphenyl phosphate), and phosphate oligomers mainly composed of bisphenol A bis(diphenyl phosphate). Among them, phosphate oligomers mainly composed of resorcinol bis((2,6-xylyl) phosphate), phosphate oligomers mainly composed of 4,4-dihydroxydiphenyl bis(diphenyl phosphate), and phosphate oligomers mainly composed of bisphenol A bis(diphenyl phosphate) are preferred.
[0147] In addition, as a suitable phosphorus-based flame retardant, a phosphazene compound can also be mentioned. As the phosphazene compound, a cyclic phenoxyphosphazene represented by the following formula (9) is preferred.
[0148]
[0149] [In the formula, m represents an integer of 3 to 25. Ph represents a phenyl group.]
[0150] Typical examples of commercially available cyclic phenoxyphosphazenes include "FP-110" manufactured by Fushimi Pharmaceutical Co., Ltd.
[0151] The content of the organophosphorus flame retardant is preferably 1 to 35 parts by weight, more preferably 2 to 30 parts by weight, and further preferably 5 to 20 parts by weight relative to 100 parts by weight of component A. If the content of the organophosphorus flame retardant is less than 1 part by weight, it is difficult to obtain a flame retardant effect, and if it exceeds 35 parts by weight, strand interruption and surge may occur during mixing and extrusion, resulting in a problem of reduced productivity.
[0152] (iii) Silicone flame retardants
[0153] The organosilicon compound used as the organosilicon flame retardant improves the flame retardancy by chemical reaction during combustion. As the compound, various compounds that have been proposed as flame retardants for aromatic polycarbonate resins can be used. It is believed that the organosilicon compound forms a structure by bonding itself or with a component from the resin during combustion, or by utilizing a reduction reaction during the formation of the structure, and particularly when using a polycarbonate resin, a high flame retardant effect is imparted.
[0154] Therefore, it is preferred to contain a group with high activity in the reaction, and more specifically, it is preferred to contain a predetermined amount of at least one group selected from an alkoxy group and hydrogen (i.e., Si-H group). The content ratio of the group (alkoxy group, Si-H group) is preferably in the range of 0.1 to 1.2 mol / 100 g, more preferably in the range of 0.12 to 1 mol / 100 g, and further preferably in the range of 0.15 to 0.6 mol / 100 g. The ratio is obtained by measuring the amount of hydrogen or alcohol produced per unit weight of the organosilicon compound by an alkali decomposition method. It should be noted that the alkoxy group is preferably an alkoxy group having 1 to 4 carbon atoms, and a methoxy group is particularly preferred.
[0155] Generally speaking, the structure of an organosilicon compound is formed by arbitrarily combining the following four types of siloxane units. That is, M unit: (CH3)3SiO 1 / 2 、H(CH3)2SiO 1 / 2 、H2(CH3)SiO 1 / 2 、(CH3)2(CH2=CH)SiO 1 / 2 、(CH3)2(C6H5)SiO 1 / 2 、(CH3)(C6H5)(CH2=CH)SiO 1 / 2 Monofunctional siloxane units such as (CH3)2SiO, H(CH3)SiO, H2SiO, H(C6H5)SiO, (CH3)(CH2=CH)SiO, (C6H5)2SiO, etc. Difunctional siloxane units such as T units: (CH3)SiO 3 / 2 、(C3H7)SiO 3 / 2 ,HSiO 3 / 2 、(CH2=CH)SiO 3 / 2 、(C6H5)SiO 3 / 2 Q unit: a trifunctional siloxane unit represented by SiO2.
[0156] The structure of the organosilicon compound used in the organosilicon flame retardant can be specifically represented by Dn, Tp, MmDn, MmTp, MmQq, MmDnTp, MmDnQq, MmTpQq, MmDnTpQq, DnTp, DnQq, and DnTpQq. Among them, the preferred structures of the organosilicon compound are MmDn, MmTp, MmDnTp, and MmDnQq, and the more preferred structure is MmDn or MmDnTp.
[0157] Here, the coefficients m, n, p, and q in the above-mentioned indicative formula are integers greater than 1 representing the degree of polymerization of each siloxane unit, and the sum of the coefficients in each indicative formula is the average degree of polymerization of the organosilicon compound. The average degree of polymerization is preferably in the range of 3 to 150, more preferably in the range of 3 to 80, further preferably in the range of 3 to 60, and particularly preferably in the range of 4 to 40. The more preferred range, the better the flame retardancy. In addition, as described below, the organosilicon compound containing a specified amount of aromatic groups also has excellent transparency and color tone. As a result, good reflected light can be obtained. In addition, when any one of m, n, p, and q is a value greater than 2, the siloxane unit with this coefficient can be two or more siloxane units with different bonded hydrogen atoms or organic residues.
[0158] The organosilicon compound may be linear or branched. In addition, the organic residue bonded to the silicon atom is preferably an organic residue having 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms. Specifically, alkyl groups such as methyl, ethyl, propyl, butyl, hexyl and decyl, cycloalkyl groups such as cyclohexyl, aryl groups such as phenyl, and arylalkyl groups such as tolyl can be cited as the organic residue. Alkyl groups, alkenyl groups or aryl groups having 1 to 8 carbon atoms are further preferred. As alkyl groups, alkyl groups having 1 to 4 carbon atoms such as methyl, ethyl and propyl groups are particularly preferred. It is further preferred that the organosilicon compound used as an organosilicon flame retardant contains an aryl group. On the other hand, silane compounds and siloxane compounds used as organic surface treatment agents for titanium dioxide pigments are significantly different from organosilicon flame retardants in their preferred form in that those that do not contain an aryl group can obtain a preferred effect. The organosilicon compound used as the organosilicon flame retardant may contain a reactive group other than the above-mentioned Si—H group and alkoxy group. Examples of the reactive group include an amino group, a carboxyl group, an epoxy group, a vinyl group, a mercapto group, and a methacryloxy group.
[0159] The content of the silicone-based flame retardant is preferably 0.01 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, and even more preferably 1 to 5 parts by weight, based on 100 parts by weight of the component A.
[0160] (iv) Halogen flame retardants
[0161] As the halogenated carbonate compound used as the halogen flame retardant, it is preferred to use a halogenated carbonate compound having a content of the structural unit represented by the following general formula (10) of at least 60 mol % of all structural units and a specific viscosity of 0.015 to 0.1.
[0162]
[0163] [In the general formula (10), X is a bromine atom, and R is an alkylene group having 1 to 4 carbon atoms, an alkylidene group having 1 to 4 carbon atoms, or -SO2-.]
[0164] In the above formula (10), R preferably represents a methylene group, an ethylene group, an isopropylene group, or -SO2-, and particularly preferably represents an isopropylene group.
[0165] The residual chloroformate terminal of the preferred brominated polycarbonate is few, and the terminal chlorine amount is preferably below 0.3ppm, more preferably below 0.2ppm. The terminal chlorine amount can be by making the sample be dissolved in methylene chloride, adding 4-(p-nitrobenzyl) pyridine, reacting with terminal chlorine (terminal chloroformate), utilizing ultraviolet visible spectrophotometer (U-3200 made by Hitachi Manufacturing) to measure it and obtain. If the terminal chlorine amount is below 0.3ppm, the thermal stability of the resin combination is better, and higher temperature molding can be carried out, and its result can provide the resin combination with better processability.
[0166] In addition, the residual hydroxyl terminal of the brominated polycarbonate is preferably small. More specifically, the terminal hydroxyl amount is preferably 0.0005 mol or less, and more preferably 0.0003 mol or less relative to 1 mol of the constituent unit of the brominated polycarbonate. The terminal hydroxyl amount can be obtained by dissolving the sample in deuterated chloroform and measuring it using the 1H-NMR method. If it is this terminal hydroxyl amount, the thermal stability of the resin composition is further improved, so it is preferred.
[0167] The halogenated carbonate compounds are commercially available, and examples thereof include tetrabromobisphenol A carbonate oligomers (trade names FG-7000 and FG-8500) manufactured by Teijin Ltd. These can be used in the present invention.
[0168] The content of the halogen-based flame retardant is preferably 5 to 35 parts by weight, more preferably 10 to 35 parts by weight, and even more preferably 10 to 30 parts by weight, based on 100 parts by weight of the component A.
[0169] (Component F: anti-drip agent)
[0170] As the anti-drip agent used as the F component in the present invention, a fluorine-containing polymer having fibril forming ability can be mentioned, and as the polymer, polytetrafluoroethylene, tetrafluoroethylene copolymers (e.g., tetrafluoroethylene / hexafluoropropylene copolymers, etc.), partially fluorinated polymers as shown in the communique of U.S. Patent No. 4379910, polycarbonate resins manufactured from fluorinated diphenol, etc. can be mentioned. Among them, polytetrafluoroethylene (hereinafter sometimes referred to as PTFE) is preferred.
[0171] The molecular weight of PTFE with fibril forming ability has extremely high molecular weight, and shows the trend that PTFE is combined with each other and becomes fibrous by external effects such as shearing force. Its molecular weight is 1,000,000~10,000,000,000 with the number-average molecular weight tried to be achieved by standard specific gravity, and is more preferably 2,000,000~9,000,000. Above-mentioned PTFE can also use the PTFE of aqueous dispersion form except solid shape. In addition, above-mentioned PTFE with fibril forming ability can also use the PTFE mixture of mixed form with other resin in order to improve the dispersibility in resin, and obtain good flame retardancy and mechanical properties.
[0172] As the commercially available product of the above-mentioned PTFE with fibril forming ability, for example, TEFLON (registered trademark) 6-J of Chemours-Mitsui Fluoroproducts Co., Ltd., Polyflon MPAFA500H and F-201 of Daikin Industries, Ltd., etc. can be enumerated. As the commercially available product of the aqueous dispersion of PTFE, Fluon D series made by Daikin Industries, Ltd., TEFLON (registered trademark) 31-JR of Chemours-Mitsui Fluoroproducts Co., Ltd., etc. can be enumerated as representative.
[0173] As the mixed form of PTFE, PTFE obtained by the following methods can be used: (1) a method of mixing an aqueous dispersion of PTFE with an aqueous dispersion or solution of an organic polymer and coprecipitating the mixture to obtain a coagulation mixture (the method described in Japanese Unexamined Patent Publication No. 60-258263, Japanese Unexamined Patent Publication No. 63-154744, etc.); (2) a method of mixing an aqueous dispersion of PTFE with dried organic polymer particles (the method described in Japanese Unexamined Patent Publication No. 4-272957); (3) a method of uniformly mixing an aqueous dispersion of PTFE with a solution of organic polymer particles. (4) a method of polymerizing monomers forming an organic polymer in an aqueous dispersion of PTFE (a method described in Japanese Unexamined Patent Publication No. 06-220210 and Japanese Unexamined Patent Publication No. 08-188653); (5) a method of uniformly mixing an aqueous dispersion of PTFE with an organic polymer dispersion, and then polymerizing a vinyl monomer in the mixed dispersion to obtain a mixture (a method described in Japanese Unexamined Patent Publication No. 11-29679). Commercially available products of these mixed PTFEs include "METABLEN A3800" (trade name) and "METABLEN A3750" of Mitsubishi Chemical Corporation.
[0174] The proportion of PTFE in the mixed form is preferably 1 to 60% by weight, more preferably 5 to 55% by weight, based on 100% by weight of the PTFE mixture. When the proportion of PTFE is within the above range, good dispersibility of PTFE can be achieved.
[0175] As the styrene monomer used for the organic polymer used in the polytetrafluoroethylene-based mixture, styrene which may be substituted by one or more groups selected from alkyl groups having 1 to 6 carbon atoms, alkoxy groups having 1 to 6 carbon atoms, and halogens, can be exemplified, for example, o-methylstyrene, m-methylstyrene, p-methylstyrene, dimethylstyrene, ethylstyrene, p-tert-butylstyrene, methoxystyrene, fluorostyrene, monobromostyrene, dibromostyrene, tribromostyrene, vinylxylene, and vinylnaphthalene, but not limited thereto. The above styrene monomers can be used alone or in combination of two or more.
[0176] The acrylic monomer used as the organic polymer used in the polytetrafluoroethylene-based mixture includes a (meth)acrylate derivative which may be substituted. Specifically, as the acrylic monomer, there can be exemplified (meth)acrylate derivatives which may be substituted with one or more groups selected from alkyl groups having 1 to 20 carbon atoms, cycloalkyl groups having 3 to 8 carbon atoms, aryl groups, and glycidyl groups, such as (meth)acrylonitrile, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, and glycidyl (meth)acrylate, maleimide which may be substituted with an alkyl group having 1 to 6 carbon atoms or an aryl group, such as maleimide, N-methyl-maleimide and N-phenyl-maleimide, maleic acid, fumaric acid, and itaconic acid, but are not limited thereto. The acrylic monomers can be used alone or in combination of two or more. Among these, (meth)acrylonitrile is preferred.
[0177] The amount of the units derived from the acrylic monomer contained in the organic polymer is preferably 8 to 11 parts by weight, more preferably 8 to 10 parts by weight, and even more preferably 8 to 9 parts by weight, relative to 100 parts by weight of the units derived from the styrene monomer. If the units derived from the acrylic monomer are less than 8 parts by weight, the coating strength may decrease, and if more than 11 parts by weight, the surface appearance of the molded article may deteriorate.
[0178] The residual moisture content of the polytetrafluoroethylene mixture of the present invention is preferably 0.5 wt% or less, more preferably 0.2 to 0.4 wt%, and further preferably 0.1 to 0.3 wt%. If the residual moisture content is more than 0.5 wt%, the flame retardancy may be adversely affected.
[0179] The manufacturing process of the polytetrafluoroethylene-based mixture of the present invention includes the following steps: forming a coating layer containing one or more monomers selected from styrene-based monomers and acrylic monomers on the outside of the branched polytetrafluoroethylene in the presence of an initiator. It is further preferred to include the following steps: drying after the step of forming the coating layer so that the residual moisture content is 0.5 wt% or less, preferably 0.2 to 0.4 wt%, and more preferably 0.1 to 0.3 wt%. The drying step can be performed by a method known in the art such as hot air drying or vacuum drying.
[0180] The initiator used in the polytetrafluoroethylene-based mixture of the present invention can be used without restriction as long as it is an initiator used in the polymerization reaction of styrene-based and / or acrylic monomers. As the above-mentioned initiator, cumyl hydroperoxide, di-tert-butyl peroxide, benzoyl peroxide, hydrogen peroxide, and potassium peroxide can be exemplified, but are not limited to these. The polytetrafluoroethylene-based mixture of the present invention can use more than one of the above-mentioned initiators according to the reaction conditions. The amount of the above-mentioned initiator is freely selected within the range of use in consideration of the amount of polytetrafluoroethylene and the type / amount of the monomer, and is preferably used in an amount of 0.15 to 0.25 parts by weight based on the total amount of the composition.
[0181] The polytetrafluoroethylene-based mixture of the present invention is produced by the suspension polymerization method according to the following steps.
[0182] First, water and branched polytetrafluoroethylene dispersion (solid concentration: 60%, polytetrafluoroethylene particle size: 0.15-0.3 μm) are charged into a reactor, and then acrylic monomer, styrene monomer and cumyl hydroperoxide as a water-soluble initiator are added while stirring, and the reaction is carried out at 80-90° C. for 9 hours. After the reaction is completed, centrifugal separation is performed for 30 minutes using a centrifuge to remove water and obtain a paste product. Thereafter, the product paste is dried at 80-100° C. for 8 hours using a hot air dryer. Thereafter, the dried product is pulverized to obtain the polytetrafluoroethylene-based mixture of the present invention.
[0183] The suspension polymerization method does not require the polymerization process based on emulsion dispersion in the emulsion polymerization method illustrated in the Japanese Patent Gazette No. 3469391, etc., so it is not necessary to use electrolyte salts for coagulating and precipitating the latex after the emulsifier and polymerization. In addition, for the polytetrafluoroethylene mixture manufactured by the emulsion polymerization method, the emulsifier and electrolyte salts in the mixture are easily mixed and difficult to remove, so it is difficult to reduce the sodium metal ions and potassium metal ions from the above-mentioned emulsifier and electrolyte salts. The polytetrafluoroethylene-based mixture (component B) used in the present invention is manufactured by the suspension polymerization method, so the above-mentioned emulsifier and electrolyte salts are not used, so the sodium metal ions and potassium metal ions in the mixture can be reduced, and thermal stability and hydrolysis resistance can be improved.
[0184] In addition, the coated branched PTFE can be used as an anti-drip agent in the present invention. The coated branched PTFE is a polytetrafluoroethylene mixture composed of branched polytetrafluoroethylene particles and an organic polymer, and has a coating layer composed of an organic polymer, preferably a polymer containing units from styrene monomers and / or units from acrylic monomers, on the outside of the branched polytetrafluoroethylene. The coating layer is formed on the surface of the branched polytetrafluoroethylene. In addition, the coating layer preferably contains a copolymer of styrene monomers and acrylic monomers.
[0185] The polytetrafluoroethylene contained in the coated branched PTFE is a branched polytetrafluoroethylene. When the contained polytetrafluoroethylene is not a branched polytetrafluoroethylene, the anti-drip effect is insufficient when a small amount of polytetrafluoroethylene is added. The branched polytetrafluoroethylene is in a particle form, preferably having a particle size of 0.1 to 0.6 μm, more preferably 0.3 to 0.5 μm, and further preferably 0.3 to 0.4 μm. When the particle size is less than 0.1 μm, the surface appearance of the molded article is excellent, but polytetrafluoroethylene with a particle size of less than 0.1 μm is not easily obtained commercially. In addition, when the particle size is greater than 0.6 μm, the surface appearance of the molded article sometimes deteriorates. The number average molecular weight of the polytetrafluoroethylene used in the present invention is preferably 1×10 4 ~1×10 7 , more preferably 2×10 6 ~9×10 6 Generally speaking, from the perspective of stability, high molecular weight polytetrafluoroethylene is more preferred. It can be used in the form of powder or dispersion.
[0186] The content of the branched polytetrafluoroethylene in the coated branched PTFE is preferably 20 to 60 parts by weight, more preferably 40 to 55 parts by weight, further preferably 47 to 53 parts by weight, particularly preferably 48 to 52 parts by weight, and most preferably 49 to 51 parts by weight relative to 100 parts by weight of the total weight of the coated branched PTFE. When the ratio of the branched polytetrafluoroethylene is within the above range, good dispersibility of the branched polytetrafluoroethylene can be achieved.
[0187] Relative to 100 parts by weight of component A, the content of component F is preferably 0.1 to 3 parts by weight, more preferably 0.15 to 2 parts by weight, and further preferably 0.5 to 1.5 parts by weight. If it is greater than this range, it leads to increased costs and sometimes insufficient processability. On the other hand, if it is less than this range, sometimes the flame retardant is insufficient. It should be noted that the ratio of the above-mentioned component F represents the amount of the anti-drip agent by net weight, and in the case of mixed PTFE, it represents the amount of PTFE by net weight.
[0188] (Component G: liquid crystal polyester resin)
[0189] The liquid crystal polyester resin used as the G component in the present invention is preferably a thermotropic liquid crystal polyester resin, which has the property that the polymer molecular chains are arranged in a certain direction in a molten state. The morphology of the above-mentioned arrangement state can be any of nematic, smectic, cholesteric and discotic, and can present more than two morphologies. In addition, the structure of the liquid crystal polyester resin can be any of the main chain type, side chain type and rigid main chain curved side chain type, and the main chain type liquid crystal polyester resin is preferred.
[0190] The morphology of the above-mentioned arrangement state, i.e., the property of the anisotropic melt phase can be confirmed by the conventional polarization inspection method using crossed polarizers. More specifically, the confirmation of the anisotropic melt phase can be implemented by using a Leitz polarizing microscope to observe the molten sample placed on a Leitz hot stage at a magnification of 40 times under a nitrogen atmosphere. When the polymer of the present invention is inspected between crossed polarizers, it transmits polarized light even in a molten static state, showing optical anisotropy.
[0191] In addition, the heat resistance of the liquid crystal polyester resin can be in any range, but the range of partial melting close to the processing temperature of the polycarbonate resin to form a liquid crystal phase is appropriate. The load deflection temperature of the liquid crystal polyester (ISO75-1 / 2 load 1.8Mpa condition) is preferably 150 to 280°C, more preferably 150 to 250°C. The above-mentioned liquid crystal polyester belongs to the so-called type II distinguished by heat resistance. In the case of having this heat resistance, compared with type I with higher heat resistance, the processability is excellent, and compared with type III with lower heat resistance, good flame retardancy can be achieved.
[0192] The liquid crystal polyester resin used in the present invention preferably contains polyester units and polyester amide units, preferably aromatic polyester resins and aromatic polyester amide resins, and liquid crystal polyester resins partially containing aromatic polyester units and aromatic polyester amide units in the same molecular chain are also preferred examples.
[0193] Particularly preferred are wholly aromatic polyester resins and wholly aromatic polyester amide resins having units derived from one or more compounds selected from aromatic hydroxycarboxylic acids, aromatic hydroxyamines, and aromatic diamines as constituent components. More specifically, the following may be mentioned: 1) a liquid crystal polyester resin synthesized mainly from one or more compounds selected from aromatic hydroxycarboxylic acids and their derivatives; 2) a liquid crystal polyester resin synthesized mainly from a) one or more compounds selected from aromatic hydroxycarboxylic acids and their derivatives, b) one or more compounds selected from aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives, and c) one or more compounds selected from aromatic diols, alicyclic diols, aliphatic diols, and their derivatives; 3) a liquid crystal polyester resin synthesized mainly from a) one or more compounds selected from aromatic hydroxycarboxylic acids and their derivatives, b) one or more compounds selected from aromatic hydroxyamines, aromatic diamines, and their derivatives, and c) A liquid crystal polyester amide resin synthesized from one or more compounds selected from aromatic dicarboxylic acids, alicyclic dicarboxylic acids and their derivatives; 4) a liquid crystal polyester amide resin synthesized mainly from a) one or more compounds selected from aromatic hydroxycarboxylic acids and their derivatives, b) one or more compounds selected from aromatic hydroxyamines, aromatic diamines and their derivatives, c) one or more compounds selected from aromatic dicarboxylic acids, alicyclic diols and their derivatives, and d) one or more compounds selected from aromatic diols, alicyclic diols, aliphatic diols and their derivatives, preferably 1) a liquid crystal polyester resin synthesized mainly from one or more compounds selected from aromatic hydroxycarboxylic acids and their derivatives.
[0194] Furthermore, a molecular weight modifier may be used in combination with the above-mentioned components as required.
[0195] Preferred examples of specific compounds used in the synthesis of the liquid crystal polyester resin used in the polycarbonate resin composition of the present invention are naphthalene compounds such as 2,6-naphthalene dicarboxylic acid, 2,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene and 6-hydroxy-2-naphthoic acid, biphenyl compounds such as 4,4'-diphenyl dicarboxylic acid and 4,4'-dihydroxybiphenyl, para-substituted benzene compounds such as p-hydroxybenzoic acid, terephthalic acid, hydroquinone, p-aminophenol and p-phenylenediamine, and their core-substituted benzene compounds (the substituents are selected from chlorine, bromine, methyl, phenyl, 1-phenylethyl), meta-substituted benzene compounds such as isophthalic acid and resorcinol, and compounds represented by the following general formula (11), (12) or (13). Among them, p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid are particularly preferred, and a liquid crystal polyester resin obtained by mixing the two is preferred. The ratio of the former is preferably in the range of 90 to 50 mol %, more preferably in the range of 80 to 65 mol %, and the latter is preferably in the range of 10 to 50 mol %, more preferably in the range of 20 to 35 mol %.
[0196]
[0197] (wherein X is a group selected from an alkylene group and an alkylidene group having 1 to 4 carbon atoms, -O-, -SO-, -SO2-, -S- and -CO-, and Y is a group selected from -(CH2) n -(n=1~4) and -O(CH2) n O-(n=1 to 4).
[0198] In addition to the above-mentioned components, the liquid crystal polyester resin used in the present invention may contain units derived from polyalkylene terephthalate that does not exhibit an anisotropic melt phase in part of the same molecular chain. In this case, the alkyl group has 2 to 4 carbon atoms.
[0199] The basic manufacturing method of the liquid crystal polyester resin used in the present invention is not particularly limited, and can be manufactured according to the known polycondensation method of the liquid crystal polyester resin. In addition, when the above-mentioned liquid crystal polyester resin is dissolved in pentafluorophenol at a concentration of 0.1% by weight at 60°C, it generally shows a logarithmic viscosity (IV value) of at least about 2.0 dl / g, for example, about 2.0 to 10.0 dl / g.
[0200] According to the above characteristics, the liquid crystal polyester resin becomes fine fibrils during injection molding, and maintains its shape during the cooling and solidification process to show a reinforcing effect on the matrix. Therefore, the liquid crystal polyester resin can be used to impart tensile strength. By using the liquid crystal polyester resin to reduce the viscosity of the resin composition, it is also possible to reduce the injection speed and resin pressure.
[0201] The content of component G is preferably 1 to 20 parts by weight, more preferably 1 to 15 parts by weight, and further preferably 2 to 10 parts by weight relative to 100 parts by weight of component A. When the content exceeds the above range and is too small, the tensile strength may be reduced. On the other hand, when the content exceeds the above range, the tensile strength may be reduced.
[0202] (Other additives)
[0203] In addition, the resin composition of the present invention may further contain other thermoplastic resins (e.g., polyarylate resins, fluororesins, polyester resins, polyphenylene sulfide resins, etc.), antioxidants (e.g., hindered phenol compounds, etc.), impact modifiers, ultraviolet absorbers, light stabilizers, mold release agents, lubricants, colorants, inorganic fillers (talc, mica, wollastonite, kaolin, etc.), etc., within the range not impairing the purpose of the present invention.
[0204] When manufacturing the resin composition of the present invention, any method can be adopted. For example, each component and any other component can be pre-mixed, and then melt-mixed and granulated. As the pre-mixed mechanism, Nauta mixer, V-type mixer, Henschel mixer, mechanochemical device, extrusion mixer, etc. can be cited. In pre-mixing, extrusion granulator, briquetting machine, etc. can also be used for granulation as appropriate. After pre-mixing, melt-mixed using a melt-mixing machine represented by a vent type twin screw extruder, and granulated using machines such as granulators. As a melt-mixing machine, Banbury mixer, mixing roller, constant heat stirring container, etc. can be cited in addition, but preferably a vent type twin screw extruder. In addition, it is also possible to adopt a method in which each component and any other component are not pre-mixed, but each is independently supplied to a melt-mixing machine represented by a twin screw extruder.
[0205] The polycarbonate resin composition of the present invention obtained as described above is usually manufactured by injection molding the pellets manufactured as described above to manufacture various products. In addition, the resin melt-kneaded by an extruder can be directly made into sheets, films, profile extrusion molded products and injection molded products without pellets.
[0206] In the above-mentioned injection molding, not only the usual molding method can be adopted, but also the injection molding methods such as injection compression molding, injection pressing molding, gas-assisted injection molding, foam molding (including molding by injecting supercritical fluid), insert molding, in-mold coating molding, heat insulation mold molding, rapid heating and cooling mold molding, two-color molding, sandwich molding and ultra-high-speed injection molding can be used to obtain molded products according to the purpose. The advantages of these various molding methods are well known. In addition, the molding can be selected from either the cold runner method or the hot runner method. In addition, the polycarbonate resin composition of the present invention can also be molded into various special-shaped extrusion moldings and sheets by extrusion molding.
[0207] Examples of molded articles using the resin composition of the present invention include electrical and electronic parts such as connectors, sockets, relay parts, coil bobbins, optical pickups, resonators, printed wiring boards, and computer-related parts; parts related to semiconductor manufacturing processes such as IC trays and wafer carriers; parts or housing materials for household electrical appliances such as computers, video recorders, televisions, irons, air conditioners, stereos, vacuum cleaners, refrigerators, rice cookers, and lighting fixtures; parts for lighting fixtures such as lamp reflectors and lamp holders; and parts for CDs, Laser Disk (registered trademark), speaker and other audio product parts; optical cable ferrules, telephone parts, fax machine parts, modems and other communication equipment parts; separation claws, heater brackets and other copier related parts; impellers, fans, gears, gears, bearings, motor parts and housings and other mechanical parts; automotive parts such as automotive mechanism parts, motor parts, motor compartment parts, electrical parts, interior parts and other automotive parts; microwave cooking pots, heat-resistant tableware and other cooking utensils; floor, wall materials and other insulation, sound insulation materials, beams, columns and other supporting materials, roof materials and other construction materials or civil engineering materials; aircraft parts, spacecraft parts, nuclear reactors and other radiation facility parts, marine facility parts, cleaning fixtures, optical equipment parts, valves, pipes, nozzles, filters, membranes, medical equipment parts and materials, sensor parts, sanitary equipment, sports goods, leisure goods, etc.
[0208] The inventors of the present invention believe that the best mode of the present invention is to focus on the preferred ranges of the above-mentioned requirements, and representative examples thereof are described in the following embodiments. Of course, the present invention is not limited to these modes.
[0209] Example
[0210] The present invention will be further described below with reference to Examples. It should be noted that the evaluation was carried out by the following method.
[0211] (Evaluation of polycarbonate resin composition)
[0212] (i) Tensile strength: The tensile strength was measured in accordance with ISO 527 using a tensile test piece obtained by the following method (tensile speed: 5 mm / min, test temperature: 23° C.)
[0213] (ii) Moisture and heat resistance: After the tensile test piece obtained by the following method is treated at 85°C and 85% relative humidity for 1000 hours, the test piece is taken out and cooled to 23°C. Next, the tensile strength (tensile strength before and after the wet heat treatment) is measured in accordance with ISO527. Then, the obtained value is substituted into the following formula to calculate the retention rate of tensile strength.
[0214] Tensile strength retention (%) = (tensile strength after wet heat treatment / tensile strength before wet heat treatment) × 100
[0215] (iii) Chemical resistance: A tensile test piece obtained by the following method was subjected to a three-point bending test method, and after being deformed by 0.7%, a cloth impregnated with Magiclean (manufactured by Kao Corporation) was placed on the piece and allowed to stand at 23°C for 96 hours to confirm whether there was any change in appearance. The evaluation was carried out according to the following criteria.
[0216] A: No change in appearance was observed.
[0217] B: Generation of fine cracks was observed.
[0218] C: Large cracks that may lead to breakage are observed.
[0219] (iv) Processability: Stability during extrusion was evaluated according to the following criteria.
[0220] A; The strands are stable during extrusion.
[0221] B: The strands were slightly unstable during extrusion, but could be pelletized.
[0222] C. The strands are very unstable during extrusion. It is difficult to granulate or there is a lot of volatile gas.
[0223] [Examples 1 to 20, Comparative Examples 1 to 11]
[0224] A mixture consisting of the components excluding component B in the composition shown in Tables 2 to 4 is supplied from the first supply port of the extruder. The above mixture is obtained by mixing with a V-type mixer. Component B is supplied from the second supply port using a side feed hopper. Extrusion is performed using a vent-type twin-screw extruder with a diameter of 30 mmφ (TEX30α-38.5BW-3V, The Nippon Steel Works, Ltd.), and melt-kneading is performed at a screw speed of 200 rpm, a discharge volume of 25 kg / h, and a vacuum degree of 3 kPa at the vent port to obtain pellets. It should be noted that the extrusion temperature is implemented at 300°C from the first supply port to the die head. After a portion of the obtained pellets is dried at 120°C with a hot air circulation dryer for 6 hours, an ISO tensile test piece for evaluation is molded using an injection molding machine at a barrel temperature of 310°C and a mold temperature of 120°C.
[0225] In addition, each component represented by a symbol in Table 1 to Table 4 is as follows.
[0226] (A ingredient)
[0227] A-1: Aromatic polycarbonate resin (polycarbonate resin powder having a viscosity average molecular weight of 22,400 produced from bisphenol A and phosgene by a conventional method, Panlite L-1225WP (product name) manufactured by Teijin Limited)
[0228] (Component B)
[0229] B-1: Glass fiber: Chopped glass fiber (manufactured by Nitto Bosho Co., Ltd.: CSG 3J-459 (product name), cut length 3 mm)
[0230] B-2: Glass fiber: flat cross-section chopped glass fiber (manufactured by Nitto Bosho Co., Ltd.: CSG 3PA-810 (product name), major diameter 28 μm, minor diameter 7 μm, cut length 3 mm)
[0231] B-3: Glass fiber: Chopped glass fiber (manufactured by Nippon Electric Glass Co., Ltd.: ECS 03T-211H (product name), cut length 3 mm)
[0232] B-4: Glass fiber: flat cross-section chopped glass fiber (manufactured by Nippon Electric Glass Co., Ltd.: ECS 03T-211-FGF (product name), major diameter 28 μm, minor diameter 7 μm, cut length 3 mm)
[0233] B-5 (Comparative Example): Glass fiber: Chopped glass fiber (manufactured by Nitto Bosho Co., Ltd.: CSG 3PE-455 (product name), cut length 3 mm)
[0234] B-6 (Comparative Example): Glass fiber: Chopped glass fiber (manufactured by Nitto Bosho Co., Ltd.: CSG 3PE-937 (product name), cut length 3 mm)
[0235] B-7 (Comparative Example): Glass fiber: flat cross-section chopped glass fiber (manufactured by Nitto Bosho Co., Ltd.: CSG 3PA-830 (product name), major diameter 28 μm, minor diameter 7 μm, cut length 3 mm)
[0236] <Gas Analysis>
[0237] 50 mg of the above glass fibers B-1, B-2, B-5, B-6 and B-7 were heated at 600°C for 12 seconds, and the resulting gas was analyzed. The gas analysis was performed by GC-MS (gas chromatography mass spectrometry) using JMS-Q1500GC manufactured by JEOL. The presence or absence of carboxylic anhydride was investigated from the resulting gas, and the evaluation was performed according to the following criteria.
[0238] In addition, 50 mg of the glass fibers B-3, B-4, B-5, B-6 and B-7 were heated at 400°C for 12 seconds, and the obtained gas was analyzed. It should be noted that the analytical equipment used was the same as that described above. The obtained gas was investigated for the presence or absence of the compound represented by the general formula (1), and the evaluation was performed according to the following criteria.
[0239] The results are shown in Table 1. The detection limit in this analytical method was 0.1 ng.
[0240] A: Carboxylic anhydride was detected
[0241] B: The compound represented by the above general formula (1) is detected
[0242] C: Carboxylic anhydride and the compound represented by the above general formula (1) were not detected
[0243] [Table 1]
[0244]
[0245] (Component C)
[0246] C-1: bisphenol A type epoxy resin (jER-1256 (trade name) manufactured by Mitsubishi Chemical Corporation, weight average molecular weight 50,000)
[0247] C-2: Bisphenol A type phenoxy resin (PKHH (trade name) manufactured by Gabriel Phenoxies, weight average molecular weight 52000)
[0248] (Component D)
[0249] D-1: Phosphorus stabilizer (triethyl phosphonoacetate JC-224 (trade name) manufactured by Johoku Chemical Industry Co., Ltd.)
[0250] D-2: Phosphorus stabilizer (trimethyl phosphate (TMP) manufactured by Daihachi Chemical Industry Co., Ltd.)
[0251] D-3: Phosphorus stabilizer (bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite SONGNOX6260PW (trade name) manufactured by Songwon International Japan Co., Ltd.)
[0252] (Ingredient E)
[0253] E-1: halogenated carbonate compound (brominated carbonate oligomer having a bisphenol A skeleton, FIREGUARD FG-7000 (product name) manufactured by Teijin Limited, bromine content = 52%)
[0254] E-2: Potassium diphenylsulfone sulfonate (KSS (trade name) manufactured by Arichem Co., Ltd.)
[0255] E-3: Cyclic phenoxyphosphazene (Rabitle FP-110T (trade name) manufactured by Fushimi Pharmaceutical Co., Ltd.)
[0256] (F component)
[0257] F-1: Anti-drip agent (polytetrafluoroethylene (Polyflon MPA FA-500H (trade name) manufactured by Daikin Industries, Ltd.)
[0258] (Ingredient G)
[0259] G-1: Liquid crystal polyester resin (liquid crystal polyester resin particles containing repeating units derived from p-hydroxybenzoic acid and repeating units derived from 6-hydroxy-2-naphthoic acid, LAPEROS A-950RX (product name) manufactured by Polyplastics Co., Ltd., melting point = 275 to 285°C)
[0260] (Other ingredients)
[0261] Release agent-1: HI-WAX HW405MP (Made by Mitsui Chemicals, Inc., low molecular weight polyethylene)
[0262] Release agent-2: Licowax E powder (manufactured by Clariant Japan Co., Ltd., montanic acid ester wax)
[0263] Colorant: A carbon black masterbatch produced by melt-mixing 100 parts by weight of four components, namely, 40 parts by weight of carbon black (CarbonBlack MA-100 (trade name) manufactured by Mitsubishi Chemical Corporation), 3 parts by weight of white mineral oil (Primal N382 (trade name) manufactured by Exxon Mobil), 0.2 parts by weight of montanic acid ester wax (Licowax Epowder (trade name) manufactured by Clariant Japan Co., Ltd.), and 56.8 parts by weight of bisphenol A type polycarbonate resin (CM-1000 (trade name) manufactured by Teijin Limited, viscosity average molecular weight 16000) using a twin-screw extruder.
[0264] [Table 2]
[0265] [Table 3]
[0266]
[0267] [Table 4]
[0268]
[0269] As can be seen from Tables 2 to 4 above, by the formulation of the present invention, a polycarbonate resin composition having excellent tensile strength, moist heat resistance, chemical resistance and processability can be obtained.
Claims
1. A polycarbonate resin composition, characterized in that The invention relates to a method of preparing a polyurethane foam having a prepreg containing 20 to 130 parts by weight of (B) glass fiber (B component) and 1 to 10 parts by weight of (C) phenoxy resin and / or epoxy resin (C component), relative to 100 parts by weight of (A) aromatic polycarbonate resin (A component), wherein the B component contains at least one compound selected from the group consisting of a surface treatment agent and a sizing agent, and a gas component obtained by heating the B component at 600° C. for 12 seconds contains a carboxylic anhydride, or a gas component obtained by heating the B component at 400° C. for 12 seconds contains a compound represented by the following general formula (1), In the general formula (1), n is an integer of 1 to 10, X each independently represents an alkylene group having 1 to 5 carbon atoms, and Y each independently represents an alkyl group having 1 to 5 carbon atoms.
2. The polycarbonate resin composition according to claim 1, characterized in that The carboxylic anhydride is 1,2,3,6-tetrahydrophthalic anhydride.
3. The polycarbonate resin composition according to claim 1, characterized in that In the compound represented by the general formula (1), X is an alkylene group having 3 carbon atoms.
4. The polycarbonate resin composition according to claim 1 or 3, characterized in that: The compound represented by the general formula (1) is 4,8,12,16-tetraoxaicosan-1-ol.
5. The polycarbonate resin composition according to any one of claims 1 to 4, wherein Component C is a bisphenol A type phenoxy resin and / or a bisphenol A type epoxy resin.
6. The polycarbonate resin composition according to any one of claims 1 to 5, characterized in that (D) a phosphorus-based flame retardant, that is, component D, is further contained in an amount of 0.01 to 3 parts by weight based on 100 parts by weight of component A.
7. The polycarbonate resin composition according to any one of claims 1 to 6, characterized in that The composition further contains 0.01 to 35 parts by weight of the component (E) which is a flame retardant and 0.1 to 3 parts by weight of the component (F) which is a drip-proof agent, based on 100 parts by weight of the component A.
8. The polycarbonate resin composition according to any one of claims 1 to 7, characterized in that The (G) liquid crystal polyester resin, ie, component G, is further contained in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the component A.
9. The polycarbonate resin composition according to claim 8, wherein The component G is a liquid crystal polyester resin containing a repeating unit derived from p-hydroxybenzoic acid and a repeating unit derived from 6-hydroxy-2-naphthoic acid. 10 . A molded article obtained by molding the polycarbonate resin composition according to claim 1 .
Citation Information
Patent Citations
Polymer powder composition containing tetrafluoroethylene polymer
JP1985258263A
Method for mixing fluoropolymer with polycarbonate
JP1988154744A
Polycarbonate having improved appearance and flame retardancy
JP1992272957A
Manufacturing method of polycarbonate resin
JP1993306336A
Aromatic copolycarbonate
JP1994172508A